IDENTIFIKASI GEN MULTIPLEX DNA PADA BAKTERI PENGHASIL ESBL DAN MRSA DARI ISOLAT ULKUS PASIEN DM - AMELLYA OCTIFANI (Yakpermas Press, 2025)
Elevated blood glucose levels in people with DM are prone to complications and can create a favourable environment for bacterial growth. Prolonged use of antibiotics leads to the possibility of resistance and it is necessary to identify resistance genes as soon as possible to reduce the prevalence of the spread of bacteria that infect diabetic wounds. The type of research used is observational with quantitative description. For the identification of DNA multiplex genes in ESBL-producing bacteria and MRSA from ulcer isolates of DM patients. The results of the study obtained 16 isolates from outpatients and inpatients as many as 63% of isolates identified s.aureus bacteria and e.coli 37%. DNA multiplex results of s.aureus bacterial isolates detected the mecA gene in 32% and the ctxm gene in 6%. In e.coli bacterial isolates, 6% ctx-m gene and 18% mecA gene were detected. Multiplex PCR method can be used to identify mec-A and ctx-m genes as coding genes of MRSA and ESBL producing bacteria in S.aureus and E.coli isolates from diabetic ulcer swabs..